Multi-system trajectories and the incidence of heart failure in the Framingham Offspring Study. - Cara E Guardino; Stephanie Pan; Ramachandran S Vasan; Vanessa Xanthakis (PLoS ONE, 2022)
Background Heart failure is a multi-system disease, with non-cardiac systems playing a key role in disease pathogenesis. Objective Investigate whether longitudinal multi-system trajectories incrementally predict heart failure risk compared to single-occasion traits. Methods We evaluated 3,412 participants from the Framingham Heart Study Offspring cohort, free of heart failure, who attended examination cycle 5 and at least one examination between 1995-2008 (mean age 67 years, 54% women). We related trajectories for the following organ systems and metabolic functions to heart failure risk using Cox regression: kidney (estimated glomerular filtration rate), lung (forced vital capacity and the ratio of forced expiratory volume in one second/forced vital capacity), neuromotor (gait time), muscular (grip strength), cardiac (left ventricular mass index and heart rate), vascular function (pulse pressure), cholesterol (ratio of total/high-density lipoprotein), adiposity (body mass index), inflammation (C-reactive protein) and glucose homeostasis (hemoglobin A1c). Using traits selected via forward selection, we derived a trajectory risk score and related it to heart failure risk. Results We observed 276 heart failure events during a median follow up of 10 years. Participants with the 'worst' multi-system trajectory profile had the highest heart failure risk. A one-unit increase in the trajectory risk score was associated with a 2.72-fold increase in heart failure risk (95% CI 2.21-3.34; p<0.001). The mean c-statistics for models including the trajectory risk score and single-occasion traits were 0.87 (95% CI 0.83-0.91) and 0.83 (95% CI 0.80-0.86), respectively. Conclusion Incorporating multi-system trajectories reflective of the aging process may add incremental information to heart failure risk assessment when compared to using single-occasion traits.